Dynamic manipulation of droplets using mechanically tunable microtextured chemical gradients - Ali J. Mazaltarim (Nature Portfolio, 2021)
Techniques to alter the surface of materials to enable transport of fluids have advanced considerably, but dynamic microdroplet transport remains a challenge. Here, the authors report the fabrication of microtextured chemical gradients on elastomer films and their use in controlled microdroplet transport.